South Africa : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
South Africa's 2005 Article IV Consultation reports that the short-term outlook is broadly favorable, with the main risks arising from a possible worsening of the external environment. The authorities plan to maintain a flexible exchange rate, and to intervene in the foreign exchange market only to accumulate international reserves when market conditions are favorable. The banking system is sound, and short-term vulnerabilities appear limited. Some pressures could arise from banks' large mortgage portfolio carrying variable interest rates.